PERAN BRAND IMAGE DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN KOPI STARBUCK DI KOTA MADIUN - Vania, Lesta; Handayani, Wahyu Prabawati Putri (Surakarta Management Journal, 2024)
This study aims to test and analyze the influence of brand image and brand awareness on Starbucks coffee purchasing decisions in Madiun City. The sample used in this study was 100 respondents of Starbucks coffee consumers in Madiun City. The sampling technique uses purposive sampling with the snowball sampling method. Data collection was carried out online by Google Form. Data analysis techniques use validity tests and reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests, coefficient of determination (R) tests, and t-tests. The results showed that (1) Brand image variables have a positive and significant effect on purchasing decisions; (2) Brand awareness has a positive and significant effect on purchasing decisions. The value of the coefficient of determination obtained is 0.589. It means that the variables of brand image and brand awareness on purchasing decisions influence 58.9% and the remaining 41.1% are influenced by other variables that are not included in this study.